Pierre Kieren's theory: the folding back process in mathematical problem solving - Utami, Rini; Setiyani, Setiyani; Sundawan, Mohammad Dadan; Sumarwati, Sri; Ferdianto, Ferry (Intelektual Pustaka Media Utama, 2025)
The learning of mathematics generally undergoes a less effective and less appealing learning process, resulting in students’ perceived lack of mastery of the material. Consequently, students’ insufficient understanding of the concepts leads to a lack of folding back. In the process of understanding, it influences individual characteristics, where two characteristics are cognitive styles: field-dependent and field-independent. The researcher aims to understand how the folding back process occurs in students with field-dependent and field-independent cognitive styles when solving story problems. This research is a descriptive qualitative study, with 2 students selected from a total of 28 students in class VII-A as subjects. The selected subjects have high mathematical abilities and are classified into the categories of field-dependent and field-independent cognitive styles. Data collection involves comprehension tests, group embedded figure test (GEFT), and interviews. Data analysis consists of stages such as data reduction, data presentation, and verification. Each subject is interviewed to verify their process of solving the given problems. The results of the research conclude that students with the field-independent cognitive style category have a better understanding of the material, concepts, and problem-solving compared to students in the field-dependent category.